Penerapan Model Pembelajaran Flipped Classroom dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Agama Islam - Saidana Saniyyah El Qory; Muhammad Fahmi; Saiful Jazil; Ulfatul Husna (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
The flow of digital developments has a positive impact on education. Therefore, teachers and students can collaborate in presenting creative and innovative learning that encourages the realization of critical thinking skills in students. This applies to every subject, including the subject of Islamic Religious Education (PAI). This study aims to explain the effectiveness of applying the flipped classroom learning model to increasing students' critical thinking skills in PAI subjects in class XII MIPA SMA Negeri 1 Krembung Sidoarjo. The research method used is the experimental method with the One Group Pretest-Posttest design to explain students' critical thinking skills after applying the flipped classroom learning model. The results of the study show that the application of the flipped classroom learning model has effectiveness in increasing the critical thinking skills of class XII MIPA students in PAI subjects. This is evidenced by the results of the Sig. (2-tailed) which is equal to 0.000. This value indicates (less than) <0.05 of the significance level in the Paired Sample T-Test. Therefore, the flipped classroom learning model can be recommended for its application to improve students' critical thinking skills in PAI subjects at school.